Blockchain for smart communities: Applications, challenges and opportunities. (15th October 2019) - Aggarwal, Shubhani; Chaudhary, Rajat; Aujla, Gagangeet Singh; Kumar, Neeraj; Choo, Kim-Kwang Raymond; Zomaya, Albert Y.
Abstract: Since the success of Bitcoin, there have been increased focus of studying the application of blockchain in a broad range of applications, such as in solutions facilitating identity privacy and transaction security using a decentralized architecture via different consensus mechanisms (e.g. proof-of-work) between different geo-located IoT devices/nodes in our increasingly digitalized society (e.g. smart city). In this paper, we survey the usage of blockchain technology for smart communities, focusing on key components of the blockchain applications. We also study the various process models used in the execution of secure transactions. Specifically, we present a detailed taxonomy on the applications, process models used, and communication infrastructure support needed to execute various applications. Highlights: Deep analysis and survey of usage of blockchain technology for smart communities. Blockchain applications, process models used, and communication infrastructure is provided. A comparative analysis of this survey with existing surveys on blockchain is presented.